ISCHIOFEMORAL IMPINGEMENT: ASSESSMENT OF MRI FINDINGS AND THEIR RELIABILITY - Ahmet Akça (Acta Ortopédica Brasileira, 2016)
Objective: To evaluate the Magnetic Resonance Imaging (MRI) findings and their validity in patients with ischiofemoral impingement syndrome (IFI). Methods: We retrospectively analyzed 55 hips. MRI findings of 30 hips were consistent with IFI syndrome. Twenty five hips had no MRI findings consistent with IFI syndrome. We compared the ischiofemoral space (IFS), quadratus femoris space (QFS), ischial angle (IA) and femoral neck angle (FNA) between the age and gender matched groups. We also analyzed edema, fatty replacement and partial or total rupture of quadratus femoris muscle. Mann Whitney U test was used to compare the data. Results: We observed atrophy in eight, fatty replacement also in eight and edema in all of the quadratus femoris muscle. QFS (p<0.001) and IFS (p<0.001) were significantly lower in patients as compared to the control group. IA (p=0.012) and FNA (p=0.010) values were significantly higher in patients compared with the control group. Conclusion: MRI findings of IFI include narrowing of QFS and IFS and increase in IA and FNA. This condition should be kept in mind for patients with hip pain. Level of Evidence III, Retrospective Study.